Perbedaan Representasi Sosial Tentang Siswa Junior antara Siswa Kelas XII SMAN A Dan SMAN B - Asri Christine Lubis; Ferdinand Prawiro (Jurnal Perkotaan, 2016)
Seniority is a social phenomenon that is naturally found in the school environment. At SMAN A, seniority has been abused by senior students. Meanwhile, at SMAN B, seniority has been applied positively. This difference indicates that there were unique meanings given to the junior students by the seniors in the two schools. This study aims to understand these differences by using social representations theory with the structural approach. The study was conducted in two stages. Free association method was used in the first stage to discover the attributes of social representation of junior students. Researchers asked 206 participants at SMAN A and 198 participants at SMAN B to write down the things that came to mind when they read the word "junior students". The second stage aims to identify the attributes of the central core and peripherals. A total of 92 participants from SMAN A and 92 participants from SMAN B were asked to fill out a questionnaire. The data were analyzed with the centrality test and chi-square test. The results show 18 attributes of social representation of junior students. At SMAN A, attributes of central core are [1] charming appearance and [2] the orientation of students and attribute of peripherals are [1] negative behaviors, [2] the targets of mistreatment, [3] unique appearance, [4] peeve, [5] new students, and [6] paltry. At SMAN B, attributes of central core are [1] charming appearance, [2] the orientation of students, [3] good relationships, and [4] positive behaviors and attributes of peripherals are [1] cool, [2] need to be nurtured, [3] new students, and [4] different generations. This results show differences in social representation of junior students in twelfth-graders at SMAN A and SMAN B. This study suggests that SMAN A make innovation in school regarding to student activities by looking up to SMAN B.